Survey data-UK female police-2016-Excel format.xlsx - Malbon, Christopher (Cranfield University, 2019)
This data was collated from over 2000 female police officers in relation to the wearing of body armour, bra type and size, discomfort and ability to perform simple task. The data relates to officers from the police forces of England and Wales only, collected in 2016
Keywords: 'body armour'; 'Bra type'; 'comfort'; 'Composite and Hybrid Materials'